1981
DOI: 10.1126/science.7291999
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside Stimulation of Axonal Sprouting in Vitro

Abstract: Bovine brain gangliosides were applied to primary and established neuronal cultures to examine the role of gangliosides in neuronal development. Media containing gangliosides enhanced the degree of axonal elongation exhibited by sensory ganglia neurons and increased the length and number of Neuro-2a neuroblastoma cell processes. Ganglioside-supplemented media caused a twofold increase in ornithine decarboxylase activity in both culture systems. These experiments suggest that gangliosides function as acceptor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
102
0
4

Year Published

1988
1988
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 379 publications
(112 citation statements)
references
References 17 publications
6
102
0
4
Order By: Relevance
“…Gangliosides are known to induce the differentiation of neuroblastoma cell lines with concomitant sprouting and extension of neurites [1,2], although the underlying molecular mechanism remains unknown [3,4]. Since others have shown that gangliosides are inhibitors of protein kinase C [5,6], it seemed possible that the two findings were related and that gangliosides might stimulate neuritogenesis by inhibiting the activity of protein kinase C. To check this hypothesis, we have tested the effect of 1-(5-isoquinolinylsulfonyl)-2-methylp~perazine (H7), a specific inhibitor of protein kinase C [7], on neurite outgrowth of neuro 2a cells.…”
Section: Introductionmentioning
confidence: 99%
“…Gangliosides are known to induce the differentiation of neuroblastoma cell lines with concomitant sprouting and extension of neurites [1,2], although the underlying molecular mechanism remains unknown [3,4]. Since others have shown that gangliosides are inhibitors of protein kinase C [5,6], it seemed possible that the two findings were related and that gangliosides might stimulate neuritogenesis by inhibiting the activity of protein kinase C. To check this hypothesis, we have tested the effect of 1-(5-isoquinolinylsulfonyl)-2-methylp~perazine (H7), a specific inhibitor of protein kinase C [7], on neurite outgrowth of neuro 2a cells.…”
Section: Introductionmentioning
confidence: 99%
“…GM1 therapy resulted in signi®cantly improved functional recovery. 23 ± 27 Therefore, gangliosides are used as neuroprotective agents for the treatment of spinal cord injury 25 as well as ischemia and degenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The expression patterns of gangliosides change during neuronal differentiation and development (2,3,6). Several studies have reported that the expression of gangliosides is regulated during nervous system development and is closely associated with neurogenesis, neural repair, and synaptic function (7)(8)(9)(10)(11)). Moreover, the expression level of gangliosides increases during retinoic acid (RA)-induced neuronal differentiation in embryonic carcinoma cells (12).…”
Section: Introductionmentioning
confidence: 99%